1930
DOI: 10.2307/1415447
|View full text |Cite
|
Sign up to set email alerts
|

A New Ambiguous Figure

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of Illinois Press is collaborating with JSTOR to digitize, preserve and extend access to The American Journal of Psychology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
5

Year Published

1967
1967
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(93 citation statements)
references
References 0 publications
2
85
0
5
Order By: Relevance
“…In all other cases, we produced them with Adobe Photoshop by copying the ambiguous figure, enhancing the features or visual detail of one of the two interpretations, and minimizing the features of the other interpretation by erasing some of the visual detail. Although some of the student participants may have encountered the figures previously, we tried to choose examples that were novel or not as familiar as some of the classic figures, such as the wife/mother-in-law (Boring, 1930) or the face/vase (Rubin, 1958) figures that are used in discussions of ambiguous figures for general psychology courses. The stimuli were pasted into Adobe Photoshop to adjust the figure sizes to a standard, which varied from Table 1 presents the mean ratings for each of these effects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all other cases, we produced them with Adobe Photoshop by copying the ambiguous figure, enhancing the features or visual detail of one of the two interpretations, and minimizing the features of the other interpretation by erasing some of the visual detail. Although some of the student participants may have encountered the figures previously, we tried to choose examples that were novel or not as familiar as some of the classic figures, such as the wife/mother-in-law (Boring, 1930) or the face/vase (Rubin, 1958) figures that are used in discussions of ambiguous figures for general psychology courses. The stimuli were pasted into Adobe Photoshop to adjust the figure sizes to a standard, which varied from Table 1 presents the mean ratings for each of these effects.…”
Section: Methodsmentioning
confidence: 99%
“…In all cases, the reversals change the meaning of the figure. We did not select figures like the Necker cube (Necker, 1832) that involved fluctuations in depth, and when possible, we tried to stay away from classic figures like Boring's wife/mother-in-law figure (Boring, 1930) or the face/vase (Rubin, 1958) that are so familiar to students. Because knowledge of an alternative interpretation of the figures has been shown by Rock and his colleagues (Girgus, Rock, & Egaz, 1977;Rock & Mitchener, 1992) to be an important aspect to seeing the reversal, we tried to use figures that were not widely distributed.…”
Section: University Of North Carolina Charlotte North Carolinamentioning
confidence: 99%
“…However, lasting changes in perceptual interpretations can also result from much briefer experiences. A classic example of this is the well-known "young woman/old woman" illusion (Boring, 1930), an ambiguous drawing which can be interpreted as either a relatively young or very old woman. Leeper (1935) found that preceding the viewing of this image with an unambiguous version of the drawing, which was not open to alternative construals, overwhelmingly biased participants' subsequent interpretation of the ambiguous figure.…”
Section: Perception Cognition and Transfermentioning
confidence: 99%
“…When considering the Boring (1930) "wife and mother-in-law" figure for use in his experimental studies, Leeper observed the aspect of the figure which depicts the face of the younger female, or "wife," to be dominant since it appeared to Ss upon 65 percent of occasions, the "mother-in-law" appearing on 35 percent. Accordingly, he prepared three "gypsy and rabbit" figures, one of which he considered to be truly ambiguous.…”
mentioning
confidence: 99%